Tackle characteristics associated with suspected concussion in female varsity rugby union: a case-control video analysis study - Shill, I. J.; Galarneau, J. M.; Hendricks, S.; Hagel, B. E.; Emery, C. A.; West, S. W. (International Journal of Performance Analysis in Sport, 2025)
The tackle is the most frequent and injurious event in rugby union. Tackle-related risk factors for concussion are identified in elite men, but may differ for women. The objective of this study was to evaluate the association between tackle characteristics and suspected concussion-related vs. non-injurious tackle events in Canadian female varsity rugby. Nacsport software was used to code 325 tackle events (46 suspected-concussion, 279 non-concussion). A penalised logistic regression with cluster-robust standard errors was used to estimate odds ratios (OR) [95% confidence intervals (95% CI)]. Ball-carrier concussion was associated with a head contact intensity of 2/4 (OR 6.5, 95% CI 1.3-31.6) and 3-4/4 (OR 48.5, 95% CI 12.1-193.7), illegal tackle (OR = 13.4, 95% CI 2.9-61.0), tap tackle (OR = 6.2, 95% CI 2.0-19.7), and down pre-contact head position (OR = 4.0, 95% CI 1.1-14.8). Tackler concussion was associated with 3 tacklers in the event (OR = 7.0, 95% CI 1.4-36.1), tap tackle (OR = 15.0, 95% CI 1.6-138.3), head contact intensity of 3-4/4 (OR = 30.6, 95% CI 5.6-168.1), and away pre-contact head position (OR = 3.0, 95% CI 1.1-7.8). Interventions aiming to reduce head impacts are needed in female rugby. Future directions should evaluate sex-related tackle characteristic differences.